Management Information System Development Concept School Database - Prananosa, Ahmad Gawdy; Wahyudi, Moch; Widodo, Suparno Eko (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to know the concept of developing a school database management information system. The model that will be used in this study is the spiral model. Each cycle includes 1) communication with users, 2) planning, 3) risk analysis, 4) prototype or engineering, 5) construction, and 6) system evaluation. The results of the study, the SIM database model of the school that was developed, still has shortcomings that must be corrected. Deficiencies at the concept development stage will be a reference for developers to improve. Suggestions from the validator were corrected and subsequently as a basis for designing the School Database SIM model at the system development stage. Conclusions, the concept of developing a school database system in the Department of Education and Culture of Musi Rawas Regency includes; a) developing a school database system for the Education Office admin (home menu, profile menu and submenus, report menu and submenu, admin menu and submenu, and logout menu), b) developing a school database system for school admin (home menu, menu and submenu profiles, menus and student submenus, educators and educational staff menus and submenus, facilities and infrastructure menus and submenus, curriculum menus and submenus, public relations menus and submenus, financial menus and submenus, report menus and submenus, and log out menus).